2006
DOI: 10.1124/jpet.106.105668
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Rat Intestinal P-glycoprotein by Spironolactone and Its Effect on Absorption of Orally Administered Digoxin

Abstract: The effect of the diuretic spironolactone (SL) on expression and function of intestinal P-glycoprotein (P-gp), as well as its impact on intestinal absorption of digoxin, was explored. Rats were treated with daily doses of 200 mol/kg b.wt. of SL intraperitoneally for 3 consecutive days. The small intestine was divided into four equal segments of ϳ25 cm, with segment I being the most proximal. Brush-border membranes were isolated and used in analysis of P-gp expression by Western blot analysis. P-gp content incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The efflux ratio of absorptive transport (M to S) was increased significantly, while the secretory transport (S to M) decreased, compared to the control. Previous studies indicated that the secretory-directed transport of other P-gp substrates, like methyprednisolone and prednisolone could be inhibited in the presence of other P-gp inhibitors, such as verapamil, diltiazem and digoxin, in rats (Molden et al, 2000;Ghanem et al, 2006;Hsiao et al, 2006). Moreover, our previous study also demonstrated that PEG 20000 reduced the efflux ratio of rhodamine123 in the intestine (Shen et al, 2008).…”
Section: Discussionmentioning
confidence: 79%
“…The efflux ratio of absorptive transport (M to S) was increased significantly, while the secretory transport (S to M) decreased, compared to the control. Previous studies indicated that the secretory-directed transport of other P-gp substrates, like methyprednisolone and prednisolone could be inhibited in the presence of other P-gp inhibitors, such as verapamil, diltiazem and digoxin, in rats (Molden et al, 2000;Ghanem et al, 2006;Hsiao et al, 2006). Moreover, our previous study also demonstrated that PEG 20000 reduced the efflux ratio of rhodamine123 in the intestine (Shen et al, 2008).…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, mechanisms other than PXR are involved in Bsep induction by spironolactone. For example, Ghanem et al [59] showed that in rats, spironolactone treatment increased p-glycoprotein expression and thus decreased intestinal absorption and liver content of digoxin. Therefore, spironolactone may be capable of altering disposition of some exogenous or endogenous compounds, such as bile acids, which might be responsible for regulation of Bsep.…”
Section: Discussionmentioning
confidence: 99%
“…The ocular biodisponibility of spironolactone and eplerenone after systemic administration has not been studied but spironolactone induces the expression of the P-glycoprotein, a drug efflux protein that regulates the bloodebrain barrier, and is one of its ligands (Ghanem et al, 2006).…”
Section: The Different Mr Antagonistsmentioning
confidence: 99%